Credit risk : from transaction to portfolio management - Kimber, Andrew (Global capital markets series., 2004)
'Credit Risk: from transaction to portfolio management' provides high level, focused analysis of the nature of credit risk in investment bank portfolio management. Written by experienced international practitioners, it offers in-depth information and advice that will help all those charged with managing credit risk at the sharp end. Credit Risk Management strives to protect the capital and reputation of the bank while preserving its franchise and optimising long-term profitability. These goals are achieved by: * Recommending suitable credit policies and guidelines * Performing due diligence on the banks' customers * Incorporating both quanitative and qualitative analysis to balance risk and return * Providing creative advice to facilitate client transactions * Coordinating legal and operational issues * Embracing technological change to enhance bank effectiveness 'Credit Risk' provides financial institutions and their staff with everything they need to know about how to control and manage credit risk. It gives sound analysis of trading strategies and complex derivative product, offers an understanding of settlement procedures and legal issues, and shows how to accurately quantify and measure related risks. Written by professionals for professionals - authors are from two of the world's largest international investment banksIn-depth, focused informationHigh level, comprehensive analysis of the subject.